The impact of the development of verbal recoding on children's early writing skills. (24th October 2011) - Adams, Anne‐Marie; Simmons, Fiona R.; Willis, Catherine S.; Porter, Sarah
<x xml:space="preserve">Abstract</x> Background. The spontaneous recoding of visual stimuli into a phonological code to aid short‐term retention has been associated with progress in learning to read (Palmer, 2000b). Aim. This study examined whether there was a comparable association with the development of writing skills. Sample. One hundred eight children (64 males) in the second year of the UK educational system (mean age 5:8 years, SD = 4 months) were recruited to the study. Methods. The children participated in tasks to assess their general cognitive abilities, reading skills, and their predominant short‐term memory (STM) strategy for retaining visually presented stimuli. On the basis of their memory profile, children were classified as either engaging in verbal recoding of the stimuli (N = 31) or not (N = 77). Writing performance was indexed as alphabet transcription, spelling, and early text production skills. Results. Children classified as verbal recoders demonstrated better spelling performance and produced more individual letters, words, and T‐units in their texts than did children who persisted with a visual memory strategy. In contrast, the alphabet transcription abilities of the groups did not differ. Hierarchical regression analyses revealed that variance in text production skills was associated with STM capacity and that moreover, significant independent variance in the number of words and T‐units in the children's texts was predicted by individual differences in verbal recoding abilities. Conclusion. The results suggest that the development of verbal recoding skills in STM may play a role in children's early progress in writing, particularly their text generation skills.